Urinary Organophosphate Metabolites and Laboratory-Derived Phenotypic Aging Acceleration in U.S. Adults: Evidence from NHANES 1999–2018 - Rubaiya Anika; Matthew Untalan; Emanuela Taioli; Stephanie Tuminello (International Journal of Environmental Research and Public Health, 2026)
Biological aging, quantified through molecular and physiological biomarkers, provides a dynamic assessment of the aging processes. Although organophosphate (OP) pesticide exposure is known to disrupt cellular and metabolic functions, causing inflammation, its relationship with phenotypic (biological) aging acceleration (PAA) remains understudied. We examined data from 1999–2008 and 2015–2018 National Health and Nutrition Examination Survey to determine the relationship between OP and PAA. Urinary levels of 6 Dialkyl-phosphate metabolites were used to assess OP exposure; participants were considered exposed if they had at least one urinary OP metabolite above the highest lower limit of detection (LLOD). Phenotypic age was estimated using BioAge R package combining nine laboratory biomarkers. PAA was derived as the residual from regressing phenotypic age onto chronological age. The association was assessed using survey-weighted linear regression. A total of 8988 participants with complete urinary, sociodemographic, and laboratory data were included; mean chronological age was 44.95 years (SE = 0.29), while mean phenotypic age was 43.19 years (SE = 0.31). In the fully adjusted model, individuals with detected OP metabolites had higher PhenoAgeAccel (β = 0.65; 95% CI: 0.14–1.17). OP metabolite detection was associated with greater PAA, extending limited literature and supporting further investigation of its implications for healthy aging.